Mapping and Development Patterns of Agricultural Production to Actualize Self-Sufficiency of Food in Yogyakarta City - Kadarso Kadarso; Rini Raharti (Fakultas Pertanian, Universitas Janabadra, 2017)
This study aims to identify potential urban farming commodities and develop urban agricultural production in order to realize food self-sufficiency in Yogyakarta City. The study used a qualitative and quantitative approach with Location Quotient analysis instrument, Dynamic Location Quotient, SWOT Analysis. Results: base area is Mergangsan, Ngampilan, Tegalrejo, Kotagede, Mantrijeron, Gondokusuman, Wirobrajan, Pakualaman, Umbulharjo, and Kraton. Non-base areas are sub-district Gedongtengen, Gondomanan, Danurejan, and Jetis. Areas that have the potential to develop faster are Mergangsan, Ngampilan, Kotagede, Danurejan, Gondokusuman and Jetis. Areas with slower development potential are Gedong Tengen, Gondomanan, Tegalrejo, Pakualaman, Mantrijeron, Wirobrajan, Umbulharjo, and Kraton. S-O Strategy is there are several sub-districts in the city of Yogyakarta have the strength of the economic base, so the potential to develop crops; optimizing the role of Field Agricultural Instructor. The W-O strategy is the promotion of farming and improvement of farm management. S-T strategy is to improve the quality of infrastructure and improve marketing efficiency. The W-T strategy is the expansion of market share; there are other non-agricultural businesses that are more promising. Key-words: urban farming, SWOT analysis, food